PERBANDINGAN RENCANA ANGGARAN BIAYA (RAB) PADA PELAKSANAAN PELAT LANTAI METODE KONVENSIONAL DENGAN PRECAST PADA BANGUNAN RUKO NORTHWEST CITRALAND SURABAYA - Wicaksana, Achmad Ari Prasetya (Universitas Negeri Surabaya, 2023)
The budget plan is one of the important documents in the implementation of construction projects. Costs are needed to calculate the requirements needed in carrying out development work and can be circumvented by changing a work item method. The process of compiling a budget plan in this study was carried out 1) volume calculations, 2) work unit price analysis, 3) cost budget plans. The work method that will be used in this study is the precast method. Selection of efficient work methods can facilitate the completion of a job. The use of the precast method has several advantages over conventional methods such as the example in the use of formwork. In addition, this study uses a quantitative method because there is data in the form of numbers that come from calculation sources with Microsoft Excel software. The results of the budget plan for the implementation of the conventional method floor slab obtained a cost of Rp. 58,886,054, while the results of the planned budget for the implementation of the precast floor slab method obtained a cost of Rp. 53,787,754. The results of the comparison of the budget plans for the two methods amounted to Rp. 5,098,300 with a comparison percentage of 9%.